KK Time Square Starbucks Coffee / Jamal Jahid... [et al.] - Jahid, Jamal; Kontuni, Cyrierine; Norjam, Emy Noralizah; Jawatin, Charlene Nita; Jaafar, Yasmyn (Faculty of Hotel and Tourism Management, 2008)
Starbucks Coffee is highly recognized Coffee shop all over the world. The sales, risk, revenue, expenses is already known by us and the products are not a secret to the Sabah community anymore. In Sabah, there are only 5 Starbucks company which is at 1 Borneo (2), Center Point, Warisan Square, and City Mall. The location of this places and Times Square is quite far, hence, we are taking this opportunity to bring this famous coffee premise into this part of Kota Kinabalu. Since there are other companies that provide this kind coffee shop concept such as Coffee Bean, we have set a clear vision, mission, and objective according to the SMART objective. Starbucks maybe thought to be a place for old people, however, we do not want this kind of thought to jeopardize our plan. So we are trying to change the outlook of people and try to attract younger generations to come to our Starbucks. In our observations, other Starbucks Company in Kota Kinabalu hires young workers. By hiring young workers, people will have a different overview on Starbucks as it is not only for old people, but for all age group. The beauty of Starbucks is that it will be a place where people can relax with good and high quality environment. Instead of wasting time doing nothing good, people can take their free time opportunity have a quality time at Starbucks. Besides, the prices can be considered as reasonable given the quality of facilities and environment provided. We have chosen the location Times Square because by the time of its full completion (2009), it will be surrounded by 348,148 citizens, increasing the number of our customers. The area which Times Square is in now is a highly developing. In other word, this location is a gold mine.